Modelling of psoriasis patient flows for the reconfiguration of secondary care services and treatments. Issue 1 (1st March 2016) - Putman, Kayne; Anstey, Alex; Harper, Paul R; Knight, Vince A
Abstract: This paper describes work in collaboration with a large dermatology directorate in South Wales to map out current patient flow and activity levels for psoriasis management. Psoriasis is a chronic skin disease that often has a high impact on patient quality of life. Clinical services for patients with moderate to severe psoriasis tend to be located in secondary care hospitals. The range of services that were studied, their geographical location in relation to the distribution of population, and the population demographics in this health board were not unique; similar profiles for these factors can be found throughout the NHS in England and Wales. The model was created to analyse patient flow through different therapies, with the aim of maximising throughput of patients, eliminating bottlenecks, improving patient access to services and improving patient safety. It was shown that reducing waiting times and improving access to phototherapy would lower overall service costs, as fewer patients would subsequently require systemic and biologic therapies. The model has been used to quantify how recent year-on-year increases in overall spend on psoriasis treatments might be slowed and eventually halted. This would require reallocation of notional cost-savings generated by reducing the rate of increase in the drug spend to fund the development of a more balanced and accessible network of more basic psoriasis services.